1987
DOI: 10.1093/nar/15.9.3907
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tetraalkyl ammonium lons on the structure of poly (rG-dC).poly (rG-dC): unexpected transitions among the Z, A and B conformations

Abstract: The conformation of the double-stranded, mixed ribodeoxyribo polynucleotide, poly (rG-dC).poly (rG-dC), has been examined in the presence of tetraalkyl ammonium ions. Tetramethyl ammonium ion stabilizes the "low salt" Z conformation (1) of the polymer from submillimolar to molar concentrations of the counterion. In the presence of tetraethyl and tetrapropyl ammonium ions the polymer exists in the low salt Z form up to 2 mM concentration of the counterions and then flips to the right hand helical A form. With t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…NMR spectroscopy studies have shown that a DNA stretch containing a ribose residue assumes the N‐type (3′endo) puckering while deoxyribose‐containing lengths are mainly in the S‐type (C2′endo) puckering. On the other hand an X‐ray fiber diffraction study on poly(rA) poly(dT) and CD measurements of poly (rG‐dC) poly (rG‐dC) have indicated that they may assume the B‐form character [98]. Recently, the B‐form of DNA‐RNA chimeras (IrCICICIC) 2 and (IrCIrCICIC) 2 in their complexes with distamycin A has been determined [99].…”
Section: High‐pressure Mediated Conformational Changes Of Ribonucleicmentioning
confidence: 99%
“…NMR spectroscopy studies have shown that a DNA stretch containing a ribose residue assumes the N‐type (3′endo) puckering while deoxyribose‐containing lengths are mainly in the S‐type (C2′endo) puckering. On the other hand an X‐ray fiber diffraction study on poly(rA) poly(dT) and CD measurements of poly (rG‐dC) poly (rG‐dC) have indicated that they may assume the B‐form character [98]. Recently, the B‐form of DNA‐RNA chimeras (IrCICICIC) 2 and (IrCIrCICIC) 2 in their complexes with distamycin A has been determined [99].…”
Section: High‐pressure Mediated Conformational Changes Of Ribonucleicmentioning
confidence: 99%
“…The thermal modifications were not reversed by decreasing again the temperature: after overnight equilibration at room temperature, the spectra did not show any change. At 0.020 M cadmium, the high temperature spectra suggested a time evolution not towards a Z-but instead an A-form similar to that presented by (G + C)-reach DNA 55 or by poly(rG-dC). 56 The spectral time evolution at 0.010 M cadmium was intermediate between that described for 0.005 and 0.020 M CdCl 2 .…”
Section: Microemulsion Experiments: Polygcmentioning
confidence: 85%
“…The sample, taken back to room temperature yielded a CD spectrum similar to that of the A-form. 55,56 For 0.070 M cadmium the B-to-Z conformational changes are almost reversible: after an overnight equilibration at room temperature the initial B-DNA spectrum was again obtained.…”
Section: Microemulsion Experiments: Polygcmentioning
confidence: 99%
“…It is known to exist in the A conformation at moderate salt concentrations and to convert to left-hand helical Z forms at low or high monovalent cation concentration (Wu & Behe, 1984). In solutions containing tetrabutylammonium ions and lacking any competing cations, the polymer can even assume a conformation that yields a circular dichroism spectrum characteristic of B-form DNA (Jayasena & Behe, 1987). Under the solution conditions employed here, however, the unassociated polymer should be firmly in the A form, at least prior to association with histones.…”
Section: Discussionmentioning
confidence: 97%